DIGITAL MARKETING TRAINING IN EFFORTS TO INCREASE SALES IN MSME BUSINESS IN METRO ATOM PASAR Baru, PD. PASAR JAYA DKI JAKARTA: DIGITAL MARKETING TRAINING IN EFFORTS TO INCREASE SALES IN MSME BUSINESS IN METRO ATOM PASAR Baru, PD. PASAR JAYA DKI JAKARTA - Tarmizi, Achmad; Shieto, Shieto (Andhara, 2022)
Micro, small and medium enterprises have been recognized as very strategic and important, not only for economic growth but also for equitable distribution of income. MSMEs also experience limited human resources. Most MSMEs have low education with minimal technical expertise, entrepreneurial and management competencies. Through digital marketing training in an effort to increase sales, it is expected to provide provisions in strengthening its competitiveness. After completing digital marketing in an effort to increase sales organized by the Community Service Team in the form of theory and practice, the training participants are expected to be able to 1) Identify the use of marketing media in MSMEs 2) Describe efforts to increase technology-based sales in MSMEs through digital marketing training 3) To Furthermore, after completing the training, the trainees are expected to be able to implement online media-based promotions so that they can improve their welfare through independent business. Keywords: Digital Marketing, Sales Increase, UMKM